Efficacy of Antibiotics in Managing Mild to Moderate Exacerbations of Bronchial Asthma in Children Under 12 Years - Mahajan, Nikhil (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Bronchial asthma is a common chronic respiratory condition in children, characterized by intermittent exacerbations. Mild to moderate exacerbations often lead to increased healthcare utilization and can be distressing for both patients and caregivers. While the primary management focuses on bronchodilators and anti-inflammatory medications, the role of antibiotics in these exacerbations remains controversial. Objective: This study aims to assess the efficacy of antibiotics in controlling mild to moderate exacerbations of bronchial asthma in children under 12 years of age. Material and Methods: A total of 40 pediatric patients aged 2 to 12 years with mild to moderate asthma exacerbations were enrolled from the Department of Pediatrics at a tertiary care hospital. Each patient underwent a detailed clinical evaluation, including medical history and physical examination. Patients were randomly assigned to receive either standard asthma management or standard management plus antibiotics. Results: The study demonstrated that children receiving antibiotics showed a statistically significant reduction in exacerbation frequency and severity compared to those receiving standard treatment alone. The findings are presented in Table 1. Conclusion: Antibiotics may play a beneficial role in the management of mild to moderate exacerbations of bronchial asthma in children under 12 years. Further studies are warranted to explore the specific indications and optimal types of antibiotics. Keywords: Bronchial asthma, children, antibiotics, exacerbations and pediatrics